Implementation of Inverter and Modbus RTU RS-485 Communication in Controlling Induction Motor Speed - Mas’ud, Ibnu; Anshory, Izza; Jamaaluddin, Jamaaluddin; Wisaksono, Arief (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2025)
As industrial technology continues to advance, the demand for efficient and automated motor control systems is increasing. Three-phase induction motors are widely used due to their durability and efficiency. However, controlling their speed remains a challenge, especially in small-scale applications without expensive systems. Therefore, a precise, affordable, and easy-to-implement motor control solution is needed. This study discusses the implementation of a three-phase induction motor speed control system using the LS G100 inverter and LS XBM-DR16S PLC through the Modbus RTU RS-485 communication protocol. The system is designed without additional expansion boards to simplify the circuit and reduce costs. The methodology used is an engineering and experimental approach, focusing on the measurement of motor electrical parameters such as actual speed (RPM), frequency, voltage, and current. Test results show that the system is capable of precisely controlling motor speed, with an average RPM accuracy of 99.6%, voltage accuracy of 97.2%, and current accuracy of 91.1%. The system has proven to be reliable and efficient for small to medium-scale industrial automation applications and facilitates real-time troubleshooting and monitoring through integrated data communication.